Synthesis of 1,2,3 –Trisubstituted- 1,2,3- Trihydro-1,3Diazepine-4,7-Diones (part3) - Hussein, F.A.; Mahmoud, M. J.; Tawfiq, M. T. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
1,3- Oxazepines, benz [1,2-e] [1,3]-oxazepines, and 3- nitrobenz [1,2-e] [1,3] - oxazepines were reacted with ammonia derivatives, H2N-Z .. to give 1,3 – diazepine -4,7- dione, benzodiazepine - 4,7- dione, and 3 – nitrobenzo -1,3- diazepine - 4,7- dione, respectively.